PEMIKIRAN POLITIK DAN DAKWAH HASAN AL-BANNA - Yuni Fadilah Rahmi (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2017)
Abstract: The Political Thought and Propagation of Hasan Al-Banna. With the problem of how politics and propaganda hasan Al-banna? and how the political contributions and propagation of hasan Al Banna in Indonesia? This research is a qualitative descriptive study. This type of research is library research because this study sought to assess and analyze a character, trying to trace his ideas through the works, the events behind the birth. The results in this study are the political thinking of Hasan al-Banna, there are at least four things, namely: ‘Urubah (Arabism), Wathaniyah (Patriotism), Qaumiyah (Nationalism), and’ Alamiyah (Internationalism). Eight pillars Politics Hasan Al-Banna is as follows: 1) Integrated between Islam and politics (religion and state), 2) Inspired of consciousness shall liberate the homeland of Islam, 3) Inspired of consciousness shall establish an Islamic government, 4) Established the existence of Muslims, 5) Based the obligation on Islamic unity, 6) Received regulatory system, 7) Criticized multiparty and party 8) Preserved minority groups and foreign elementsHasan Al-Banna thought about propaganda. Da’wah done by Hasan al- Banna is as follows: 1. Forming Jama’ah Islamiyah (Al-Ihkwanul Muslims) 2. Preaching to people who do not go to the mosque to come into their homes, 3. Propagation not only through the pulpit but also through books, newspapers and magazines, 4. Propagation among campus. The contribution of Hasan al-Banna in politics and propaganda in Indonesia. Hasan al-Banna through the Muslim Brotherhood has spread its network at that time, also raised supports and other Arab countries to support the independence of Indonesia. The Muslim Brotherhood’s role in the independence of Indonesia, it can still be traced in the article titled Brotherhood and Indonesia. In the first-order election reform later appeared Islamic parties who use the name Masjumi, such as the New Masjumi Party and the Indonesian Islamic Political Party Masjumi (PPII Masjumi). The influence of the Muslim Brotherhood to the political thinking PKS in Indonesia is very dominant through the thought process that is carried by the alumni of universities in the Middle East. The Muslim Brotherhood has an influence on political thinking MCC ranging from the establishment of the transform of the missionary movement / MT becomes a party.